Expansive Learning in Inter-Institutional Communities of Practice for Teacher Educators and Policymakers - Guberman, Ainat; Avidov-Ungar, Orit; Dahan, Orit; Serlin, Ruth (Frontiers in Education, 2021)
The current study deals with participation in inter-institutional Communities of Practice (CoP) (Wenger, 1998) as a form of professional learning for experienced teacher educators who hold leadership positions in their institutions. In these CoPs, collaboration between teacher educators and policymakers resulted in expansive learning, which is the creation of new practical and theoretical knowledge, and a change of practice rather than adoption of knowledge constructed elsewhere. The current study describes three such communities, the expansive learning cycles that each of them triggered, and shared characteristics that may have contributed to these outcomes. The multiple case study methodology was employed. Data sources were interviews with thirteen participants (coordinators, Ministry of Education representatives and additional members from each CoP), and documents (such as meeting minutes and research papers) that were produced in each CoP. The findings show that expansive learning occurred due to a shared vision, reflective and critical dialogue, trusting relationship, and mutual support among participants. Furthermore, the inter-institutional composition of the CoPs, and the influential position of the participants within their respective organizations enabled them to introduce coordinated changes that transformed their practice at the individual, organizational and national levels.